Расчет допусков разрядных цепей высоковольтных импульсных испытательных устройств - Петков, Александр Александрович (НТУ "ХПИ", 2008)
В работе рассмотрен выбор допусков элементов разрядной цепи по известным допускам на контролируемые параметры импульса тока. Приведены соотношения и рассмотрена методика расчетов допусков.

In the work, selection of tolerance of test device digit circuit's elements under known tolerance for controllable parameters of a current pulse is considered. Relationships are presented, a tolerance calculation technique introduced.
Calculations of tolerance of high-voltage test device digit circuits
Keywords: методика расчета; испытание; высоковольтные импульсные устройства; разрядные цепи; pulse; digit circuits; tolerance; test device; controlled parameters